Content networking in the mobile Internet - Dixit, Sudhir; Wu, Tao, 1971- (Wiley-Interscience, 2004)
Presents a combined view of content and wireless technologies useful to both the industry and academiaOffers a good mix of theory and practice to understand the internal working of the wireless/mobile content delivery networksBridges the gap between the wireless and content research communitiesFocuses not only on the latest technology enablers for speedier content delivery in the mobile Internet, but also on how to integrate them to provide workable end-to-end solutions.